Anterior cruciate ligament‐ and hamstring tendon‐derived cells: in vitro differential properties of cells involved in ACL reconstruction. (11th March 2015) - Ghebes, Corina Adriana; Kelder, Cindy; Schot, Thomas; Renard, Auke J.; Pakvis, Dean F. M.; Fernandes, Hugo; Saris, Daniel B.
Abstract: Anterior cruciate ligament (ACL) reconstruction involves the replacement of the torn ligament with a new graft, often a hamstring tendon (HT). Described as similar, the ACL and HT have intrinsic differences related to their distinct anatomical locations. From a cellular perspective, identifying these differences represents a step forward in the search for new cues that enhance recovery after the reconstruction. The purpose of this study was to characterize the phenotype and multilineage potential of ACL‐ and HT‐derived cells. ACL‐ and HT‐derived cells were isolated from tissue harvest from patients undergoing total knee arthroplasty (TKA) or ACL reconstruction. In total, three ACL and three HT donors were investigated. Cell morphology, self‐renewal potential (CFU‐F), surface marker profiling, expression of tendon/ligament‐related markers (PCR) and multilineage potential were analysed for both cell types; both had fibroblast‐like morphology and low self‐renewal potential. No differences in the expression of tendon/ligament‐related genes or a selected set of surface markers were observed between the two cell types. However, differences in their multilineage potential were observed: while ACL‐derived cells showed a high potential to differentiate into chondrocytes and adipocytes, but not osteoblasts, HT‐derived cells showed poor potential to form adipocytes, chondrocytes and osteoblasts. Our results demonstrated that HT‐derived cells have low multilineage potential compared to ACL‐derived cells, further highlighting the need for extrinsic signals to fully restore the function of the ACL upon reconstruction. Copyright © 2015 John Wiley & Sons, Ltd.